2014
DOI: 10.1007/s11010-014-2220-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin attenuated the effect of expression of β1 integrin in PAN-treated podocytes by inhibiting reactive oxygen species

Abstract: It is well accepted that β1 integrin plays a key role in maintaining normal podocytes form and functions; however, its mechanism of the potential protective effect remains unclear. Furthermore, the investigation and understanding of the non-lipid-dependent renal protection of Statins in addition to well-known lipid-lowering effect may provide the therapeutic utility and ultimately improve clinical outcome for patients with renal diseases. In the present study, we investigated the effect and mechanism of fluvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Rosuvastatin attenuated angiotensin II-dependent increases in NADPH oxidase activity and reactive oxygen species (ROS) generation in cultured podocytes [65]. In line with these findings are reports that fluvastatin is able to attenuate injury induced by PAN and to increase the production of β1-integrin in human podocytes in vitro, which is thought to be an ROS activity-inhibiting mechanism [66,67]. Rosuvastatin has also been found to display pro-survival activities in injured podocytes through a p21-dependent anti-apoptotic pathway [68].…”
Section: -Hydroxy-3-methylglutaryl-coenzyme a Reductase Inhibitorsmentioning
confidence: 56%
See 1 more Smart Citation
“…Rosuvastatin attenuated angiotensin II-dependent increases in NADPH oxidase activity and reactive oxygen species (ROS) generation in cultured podocytes [65]. In line with these findings are reports that fluvastatin is able to attenuate injury induced by PAN and to increase the production of β1-integrin in human podocytes in vitro, which is thought to be an ROS activity-inhibiting mechanism [66,67]. Rosuvastatin has also been found to display pro-survival activities in injured podocytes through a p21-dependent anti-apoptotic pathway [68].…”
Section: -Hydroxy-3-methylglutaryl-coenzyme a Reductase Inhibitorsmentioning
confidence: 56%
“…Mitochondrial function [65], β-integrin [66,67] VEGF-R blocker Positive (diabetes) [86,87], negative (other glomerular disease) [80,81,88,89] Apoptosis, podocyte effacement, nephrin [79] PPARγ, peroxisome proliferator-activated receptor gamma; RAAS, renin-angiotensin-aldosterone system; ACE, angiotensin-converting enzyme; AT1-R, angiotensin II type 1 receptor; HMG-CoA reductase, 3-hydroxy-3-methylglutaryl-CoA lyase reductase; VEGF-R, vascular endothelial growth factor receptors; SMPDL-3b, sphingomyelin phosphodiesterase, acid-like 3B…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%
“…Whereas the expression of integrin β1 in podocyte was considered negatively correlated with the severity of proteinuria . Elevated expression of TGF‐β1 or ROS induced decreased expression of integrin β1, resulting in the production of proteinuria . In contrast to the other β subunits, the integrin β4 subunit contains an exceptionally large cytoplasmic domain comprising several major tyrosine phosphorylation sites and thus regulates multiple intracellular signalling pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes play a crucial role in maintaining the permeability of the glomerular filtration barrier [14], and podocyte injury is present in many types of human and experimental glomerular diseases, including HBV-GN [4, 15-17]. Moreover, a decreased number of podocytes per glomerulus is the strongest predictor of renal disease progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of integrin expression in podocytes demonstrated that α3β1 integrin is the major integrin on the surface of podocytes in humans [27] and rats [28]. This integrin is responsible for cell adhesion and signal transduction between podocytes and the extracellular matrix (ECM) of the glomerular basement membrane (GBM) [14]. Previous studies have shown that the absolute number and relative density of podocytes are reduced in HBV-GN [4], although the precise mechanism of this effect is unknown.…”
Section: Discussionmentioning
confidence: 99%